Effect of Potassium Phosphate Content in Aluminosilicate Matrix on Mechanical Properties of Carbon Prepreg Composites - Kohoutová, Eliška; Hájková, Pavlína; Kohout, Jan; Soukup, Aleš (Materials (Basel, Switzerland), 2021)
Six matrices based on alkali-activated aluminosilicate with different amounts of potassium phosphate were prepared for the production of six-layer composite plates. The addition of potassium phosphate in the matrix was 2 wt%, 4 wt%, 6 wt%, 8 wt% and 10 wt% of its total weight. The matrix without the potassium phosphate was also prepared. The aim of this study was to determine whether this addition has an effect on the tensile strength or Young's modulus of composites at temperatures up to 800 °C. Changes in the thickness and weight of the samples after this temperature were also monitored. Carbon plain weave fabric was chosen for the preparation of the composites. The results show that under normal conditions, the addition of potassium phosphate has no significant effect on the mechanical properties; the highest measured tensile strengths were around 350 MPa. However, at temperatures of 600 °C and 800 °C the addition of potassium phosphate had a positive effect, with the tensile strength of the composites being up to 300% higher than the composites without the addition. The highest measured values of composites after one hour at 600 °C were higher than 100 MPa and after 1 h at 800 °C higher than 85 MPa.
Keywords: tensile strength; inorganic matrix; prepreg; composite; phosphate; aluminosilicate